Places in Need : The Changing Geography of Poverty - Allard, Scott W. (Book collections on Project MUSE., 2017)
"Americans think of suburbs as prosperous areas that are relatively free from poverty and unemployment. Yet, today more poor people live in the suburbs than in cities themselves ... Rising suburban poverty has not coincided with a decrease in urban poverty, meaning that solutions for reducing poverty must work in both cities and suburbs. Allard notes that because the suburban social safety net is less developed than the urban safety net, a better understanding of suburban communities is critical for understanding and alleviating poverty in metropolitan areas."